Is Targeting Nerve Growth Factor Antagonist a New Option for Pharmacologic Treatment of Low Back Pain? A Supplemental Network Meta-Analysis of the American College of Physicians Guidelines - Cao, Ziqin; Li, Qiangxiang; Guo, Jia; Li, Yajia; Wu, Jianhuang (Frontiers in Pharmacology, 2021)
Objective: It has been found that targeting nerve growth factor antagonists (ANGF) have excellent effects in the treatment of chronic pain, and the current pharmacologic treatments have very limited effects on low back pain (LBP). Thus we conducted this network meta-analysis (NMA) to study the efficacy and safety of ANGF for the treatment of LBP, and to guide for clinical practice and further research. Method: PubMed, Scopus, Embase, CNKI, and the Cochrane Library were searched from January 1980 to March 2021. A frequentist framework network meta-analysis with random-effect model was performed. Ranking effects were calculated by surface under the cumulative ranking analysis (SUCRA) and clusterank analysis. Results: This NMA identified 30 studies, involving 9508 patients with LBP. ANGF reported both superior effect on pain relief (SUCRA 82.1%, SMD 0.89, 95% CI [(0.26,1.51)]) and function improvement (SUCRA 77.3%, SMD 0.93, 95% CI [(0.27,1.58)]) than placebo, and did not showed any higher risk of treatment-emergent adverse effects (RR 1.11, 95% CI [(0.97,1.27)])or serious adverse effects (RR 1.03, 95% CI [(0.54,1.97)]), but it was associate with a special risk of rapidly progressive osteoarthritis. ANGF displayed the greatest potential to be the most effective and safest treatment (cluster-rank value for function improvement and safety: 4266.96, for pain relief and safety: 4531.92). Conclusions: ANGF could relief pain and improve function effectively and are superior than other traditional drugs recommended by guidelines. Although no significant difference in tolerability and safety between ANGFs and placebo was found, the rapid progression of original osteoarthritis which may be related to the use of ANGFs still needs special attention and furtherly verification by clinical trials.